Studying Yarn Incorpectiveness Operated on the Improved Exhaust Extractor (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article studies the friction force field and the design of the exhaust cylinder of drafting devices, the effect of the design of rollers and corrugated cylinder on the friction force field. New designs of a corrugated cylinder are proposed that improve the field of friction forces. The optimization parameters of the new fume hood are determined and proposed. In existing designs of drafting devices and devices, improved control over the movement of fibers is achieved in various ways, for example, by installing additional straps, rollers, clutches, guides, trays, etc. A common drawback of this design is that by correcting one drawback, others are promoted, for example, the design of the assembly becomes more complicated or maintenance is difficult, etc.